“Biologic” treatment for meniscal repair - Cengiz, I. F. (2017)
The menisci are vital components of a healthy knee. Meniscal injuries are frequent, and their complete healing is a clinical challenge. Biologics have been studied extensively to investigate their roles and effects to augment tissue healing. This chapter aims to describe the clinical application technique of autologous bone marrow-derived fibrin clot for meniscal repair and overviews the use of platelet-rich plasma for meniscal regeneration.